Engineering Optimization with Membrane Algorithms - Gheorghe, Marian; Zhang, Gexiang; Pérez-Jiménez, Mario J (Real-Life Applications with Membrane Computing, 2017)
In this chapter are described engineering applications of the membrane algorithms introduced in Chap. 10.1007/978-3-319-55989-6_3. The engineering problems we consider are the following: radar emitter signal analysis, digital image processing, controller design, mobile robot path planning, constrained manufacturing parameter optimization problems, distribution network reconfiguration and electric power system fault diagnosis.